Inadequate PTH Response to Hypocalcemia in People Living with HIV - Noe, Sebastian; Jonsson-Oldenbuettel, Celia; Jaeger, Hans; Schoenitzer, Veronika; Balogh, Annamaria; Wolf, Eva; Arc HIV study group (Current HIV Research, 2022)
Background: Small experimental studies suggest that PTH-secretion following hypocalcemia might be blunted in people living with HIV. Objective: The aim of the study was to estimate the frequency of inadequately low concentrations of parathyroid hormone in the presence of hypocalcemia in people living with HIV. Methods: This was a retrospective study that was conducted among PLWH enrolled in the ongoing ArcHIV study between 2016 and 2017. PLWH with routine measurements for both calcium and parathyroid hormone levels were included in this analysis. The proportion of patients with a combination of low levels of both calcium and parathyroid hormone was the primary endpoint of this analysis. Result: 496 PLWH were included (mean age 47.1 (± 10.2) years, 393 (79.2 %) men). In 14 (2.8 %) PLWH, low calcium levels with low levels of PTH were observed in the assessment conducted in both years. Undergoing a tenofovir disoproxil-containing treatment in both years was the only explanatory variable significantly associated with inadequately low levels of PTH in the presence of hypocalcemia in both years (OR 4.3 [CI95: 1.4; 16.0]). Conclusion: The combination of low levels of both calcium and PTH was found more frequent in our study sample when compared to what is expected from the general population. Interestingly, undergoing a tenofovir disoproxil-containing therapy was associated with this combination throughout both the years.
Keywords: tenofovir disoproxil